Dacha Idylls : Living Organically in Russia's Countryside - Caldwell, Melissa L., 1969- (Book collections on Project MUSE., 2011)
Dacha Idylls is a lively account of dacha life and how Russians experience this deeply rooted tradition of the summer cottage amid the changing cultural, economic, and political landscape of postsocialist Russia. Simultaneously beloved and reviled, dachas wield a power that makes owning and caring for them an essential part of life. In this book, Melissa L. Caldwell captures the dacha's abiding traditions and demonstrates why Russians insist that these dwellings are key to understanding Russian life. She draws on literary texts as well as observations from dacha dwellers to highlight this endu.